Can Levodopa Challenge Testing Predict the Effect of Deep Brain Stimulation? One-Year Outcomes in a Chinese Cohort - Lin, Wei; Shi, Dongliang; Wang, Dan; Yang, Likun; Wang, Yuhai; Jin, Lingjing (Frontiers in Aging Neuroscience, 2021)
Objective: Our study examined whether levodopa challenge test (LCT) results could predict quality of life (QoL) outcomes after surgery to implant subthalamic nucleus deep brain stimulation (STN-DBS) electrodes to treat advanced Parkinson’s disease (PD). Methods: Forty patients with STN-DBS underwent follow-up 1 year after implantation surgery to analyze the correlation between preoperative levodopa impact test results and postoperative Unified Parkinson’s Disease Rating Scale (UPDRS) III motor score, postoperative PD Questionnaire-39 (PDQ-39) score, and PDQ-39 improvement. Results: Improvements in QoL were associated with several preoperative characteristics including preoperative UPDRPS-III tremor, UPDRPS-III tremor (off-60), UPDRPS-III tremor (off-120), MMSE, and PDQ-39 before surgery (all P<0.05). A logistic regression model using preoperative MMSE (odds ratio [OR] 0.342, 95% confidence interval [CI] (0.051-2.297), preoperative UPDRPS-III tremor (OR 2.099, 95% CI 0.585-7.535) , UPDRPS-III tremor (off-60) (OR 1.316, 95% CI (0.804-2.154), UPDRPS-III tremor (off-120) (OR 0.913, 95% CI 0.691-1.207), correctly classified 88.5% of patients. Conclusion: LCT results cannot predict the effect of DBS; however, the test can be incorporated into a regression prediction model to the quality of life of PD patients after DBS with other preoperative factors.